Developing and implementing circular economy business models in service-oriented technology companies. (10th March 2018) - Heyes, Graeme; Sharmina, Maria; Mendoza, Joan Manuel F.; Gallego-Schmid, Alejandro; Azapagic, Adisa
Abstract: The service sector has the potential to play an instrumental role in the shift towards circular economy due to its strategic position between manufacturers and end-users. However, there is a paucity of supporting methodologies and real-life applications to demonstrate how service-oriented companies can implement circular economy principles in daily business practice. This paper addresses this gap by analysing the potential of service-oriented companies in the information and communication technology (ICT) sector to build and implement circular economy business models. To this end, the Backcasting and Eco-design for the Circular Economy (BECE) framework is applied in an ICT firm. BECE, previously developed and demonstrated for product-oriented applications, has been developed further here for applications in the service sector. By shifting the focus from a product-oriented approach to a user-centred eco-design, the paper shows how ICT firms can identify, evaluate and prioritise sustainable business model innovations for circular economy. The two most promising business model innovations are explored strategically with the aim of designing circular economy models consistent with the company's priorities of customer satisfaction and profitability. The findings suggest that ICT companies may be able to support the deployment of a circular economy in the service-oriented technology sector. Importantly, micro and small organisations can play a fundamental role if provided with macro-level support to overcome company-level barriers. Finally, the BECE framework is shown to be a valuable resource to explore, analyse and guide the implementation of circular economy opportunities in service-oriented organisations. Further research to verify the application of the findings to other service-oriented organisations is recommended. Highlights: Principles of circular economy is applied in service-oriented technology sector. New circular economy framework "BECE" is tested in an ICT company. The service-oriented technology sector can support the transition towards CE. Micro-sized business can play a role in the CE, if barriers are overcome. The case company's take-up of BECE shows potential for CE rollout.